Development of a collaborative material management system for offshore platform projects using agent technology. (February 2017) - Han, Duanfeng; Zhou, Qinghua; Li, Jinghua; Wang, Jiaxuan; Yang, Boxin; Sun, Miaomiao
Accuracy management of production materials plays an important role in offshore platform projects. To improve both the efficiency and accuracy of material management in offshore platform projects, a novel material management system characterized by the notion of a material information unit was proposed in light of a review of the industrial Internet of Things and multi-agent technology. The material information unit is used to carry data on production materials and serve as a basic information unit in the system. Furthermore, agents of different functions are employed to tackle assorted tasks. Using this system, material information can be precisely recorded, tracked, and traced during the manufacture of offshore platforms. In addition to this system, an algorithm targeting at multi-agent negotiation is designed. Finally, a prototype system is developed to verify the feasibility and efficiency of this material management process.